Effects of human resource practices towards employee retention among Sharp Manufacturing Corporation (M) Sdn. Bhd. permanent administrative staffs / Liyana Ayu Abdul Wahid - Abdul Wahid, Liyana Ayu (Faculty of Business and Management, 2020)
The purpose of this research is to study the effects of Human Resource practices towards employee retention among Sharp Manufacturing Corporation (M) Sdn. Bhd (SMM) permanent administrative staffs. This research is to examine the relationship between independent variables (recruitment and selection, training and career development, performance appraisal and compensation and benefits) and dependent variable (employee retention). The questionnaires were distributed traditionally to the respondents which is permanent administrative staffs at SMM by using simple random sampling technique. The Statistical Package for Social Science Version 22 (SPSS V22) was employed to analyses the data and obtain answers for the research questions. To answer the research questions, the researcher conducted few analyses namely; Reliability Analysis, Descriptive Statistic Analysis, Frequency Distribution Analysis, Pearson Correlation Analysis and Multiple Regression Analysis. The data analysis is obtained in order to meet the objective of the study which is to determine the relationship between recruitment and selection, training and career development, performance appraisal and compensation and benefits with employee retention. This study also identifies the most impactful factor that influences employee retention in manufacturing industry and result from this study shows the most impactful factor towards employee retention is compensation and benefits. Therefore, the organizations need to give full commitment to ensure compensation and benefits offered able to retain employees in the organization. Lastly, the researcher hopes that this study will help the organization to gain competitive advantage positions in the industry by retain their valuable employee in the organization.